Boosting Oxygen Reduction via Integrated Construction and Synergistic Catalysis of Porous Platinum Alloy and Defective Graphitic Carbon. (25th October 2021) - Huang, Lei; Su, Ya‐Qiong; Qi, Ruijuan; Dang, Dai; Qin, Yanyang; Xi, Shibo; Zaman, Shahid; You, Bo; Ding, Shujiang; Xia, Bao Yu
Abstract: Integrated fabrication through the strong interaction between catalyst and carrier is crucial to realize efficient oxygen electrocatalysis for fuel cells. We report herein a porous Pt‐rich alloy encapsulated by graphitic carbon via integration engineering, where a synergistic catalysis between ternary PtCuCo alloy and graphitic Co‐N‐C results in the optimized reaction pathway and improved oxygen reduction reaction (ORR) performance. The hybrid catalyst PtCuCo@Co‐N‐C delivers a mass activity of 1.14 A mgPt −1 at 0.9 V vs. RHE and a peak power density of 960 mW cm −2 in the full‐cell assessment, outperforming commercial Pt/C catalyst (0.12 A mgPt −1 and 780 mW cm −2 ). Experimental results combined with theoretical simulations suggest that the mutual assistance between porous Pt alloy and Co‐N‐C accounts for the enhanced catalytic performance. Such integrated engineering concept is significant for strengthening the anti‐corrosion capabilities and improving the ORR performance of Pt‐based catalysts. Abstract : A porous platinum‐rich alloy encapsulated by graphitic carbon results in improved oxygen reduction reaction (ORR) performance as a result of the interaction between the ternary PtCuCo alloy and graphitic Co‐N‐C units.